Waste to wealth: optimizing novel pectin acid extraction from honeydew (cucumis melo l. var. inodorous) peels as a potential halal food thickener - Siti Radhiah Omar; Nurul Afiqah Md Hamsan; Muhammad Najib Abdullah (Med Crave, 2024)
Non-Indexed Publication